Synthesising physical literacy research for ‘blank spots’: A Systematic review of reviews - Carl, Johannes; Jaunig, Johannes; Kurtzhals, Mette; Müllertz, Alberte L.O.; Stage, Anna; Bentsen, Peter; Elsborg, Peter (Journal of Sports Sciences, 2023)
The holistic concept of physical literacy (PL) has gained considerable attention worldwide and integrates different determinants (e.g., physical, affective, and cognitive) of physical activity. The purpose of this systematic review (PROSPERO registration: CRD42022312764) was to broadly synthesise PL research and determine “blank spots”. We performed standardized searches for PL reviews in 23 databases. Inclusion criteria were English language, any review with a systematized search, publication by June 2023 and PL relevance in an article’s main body. The content and insights of the identified reviews were assigned to six literature-driven “problem fields”: (i) theory/concept, (ii) measurement/levels/trends, (iii) determinants, (iv) outcomes, (v) interventions, and (vi) policy. We employed nine items for assessing the methodological quality of the reviews (including six items from AMSTAR-2). The screening resulted in an inclusion of 41 PL reviews of different methodology. Existing reviews most frequently analysed aspects of measurement (n = 20) as well as theory/definition (n = 19), followed by interventions (n = 17). In contrast, determinants (n = 6), outcomes (n = 5) and policy aspects (n = 4) were discussed less often. Accordingly, the major “blank spots” are: empirical studies on determinants and outcomes; PL levels and trends; pivotal moderators of interventions; and policy aspects. We recommend the scientific community to address these to move the field forward.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Active lifestyle; competence; education; health; physical activity; sport